Study of a metal hydride based thermal energy storage system using multi-phase heat exchange for the application of concentrated solar power system. (18th August 2021) - Yao, Jing; Zhu, Pengfei; Guo, Leilei; Yang, Fusheng; Zhang, Zaoxiao; Ren, Jianwei; Wu, Zhen
Abstract: Thermal energy storage system is of great significance for the concentrated solar power system to keep the balance between power generation and demand. Metal hydride based thermal energy storage system is regarded as a promising method due to its good reversibility, low cost, and no by-product. Multi-phase heat exchange has much higher heat transfer coefficient than single-phase fluid heat exchange, thus facilitating the steam generation. In this study, a two-dimensional model of the metal hydride reactor using multi-phase heat exchange is proposed to estimate the performance and its feasibility of application in the concentrated solar power system. The results show that the velocity of the heat transfer fluid should match well with the thermal conductivity of the metal hydride bed to maintain the heat flux at a relatively constant value. The match of thermal conductivity of 3 or 5 W/(m·K) and fluid velocity of 0.0050 m/s results in the heat flux up to about 19 kW/m 2, which is increased by 3 orders of magnitude than single-phase heat exchange. In the thermal energy storage system, the reheating cycle is recommended to improve the utilization of the thermal energy. The efficiency of the system could be improved from 18.4% to 30.8% using the reheating cycle. The increased efficiency is comparable to the previously reported efficiency of 39.2%. Besides, the operation strategy of raising the steam temperature by increasing the hydrogen pressure or the superheater temperature is suggested for the system to obtain higher efficiency. Graphical abstract: Image 1 Highlights: A model of MHR using multi-phase heat exchange is proposed for CSP application. Multi-phase flow has much better heat transfer behavior than single-phase flow. The efficiency of the MH-TES system is increased by 12.4% through reheating cycle. The application of the proposed MHR as TES unit in the CSP is discussed.